Learning style awareness and academic performance of students - Arunodaya, Barman (2014)
Introduction: Preferred approach to learning is one‘s own learning style. Learning style varies from individual to individual. When students learn in different ways; their preferred may be an important determinant of their academic performance. This study intends to explore this approach among the nursing students in Kolej Poly-Tech MARA. Methods: It was pre-test/post-test experimental study. Learning style preferences of nursing students were identified using a VARK learning style inventory. Students were informed of their preferred learning style and how to utilize their learning style strengths to improve learning for better academic performance in a one day workshop. Academic achievements of students in terms of GPA for the three consecutive examinations, two held before and one held after the workshop, were collected from the academic departments. Repeated measure ANOVA was done to compare the GPAs obtained by the students in those three examinations. Results: The study group of nursing students demonstrated different learning styles, with approximately half having a single predominant style preference. There was a significant improvement in the students‘ performance after the intervention (F (1.69,506.92) = 237.22, p<0.001). Discussion: Students‘ awareness of their strengths such as learning style preferences and how to utilize their strengths may improve their academic performance. Students should have awareness of their learning style and how to maximize their learning potential in the very early days of enrolment in the academic institution.